Governance Of Innovative Public-Private Partnerships, Focused On The Sustainable Development Goals: Experience Of African Countries - (:unkn) unknown (My University, 2023)
Public-private partnerships (PPPs) are popular globally, but their performance sparks debates. Indeed, as a strategic tool, these PPPs have emerged as potential catalysts for innovation and the achievement of Sustainable Development Goals (SDGs), thus highlighting the urgent need for effective and innovative public governance. This study aims to closely examine how innovation within PPP governance can significantly contribute to achieving the SDGs, focusing on insights from PPP experiences in Africa to identify best practices and lessons learned. It employs a Grounded Theory Analysis based on case studies of various PPPs focused on SDGs concluded between 2017 and 2023 in 21 African countries to develop our governance model, geared towards creating a specific understanding framework for PPPs in Africa, capturing the complexity of dynamics between public and private actors, success factors, challenges faced, and, most importantly, how governance innovation can be integrated to optimize PPPs' contribution to the SDGs. The results of this analysis indicate that "PPP Governance Management" is necessary to provide a structural and decision-making framework to help public and private partners collaborate, innovate, and create synergies to achieve project goals in a compliant and strategic manner. This study aims to actively contribute to enhancing the decision-making capacities of stakeholders.
Keywords: African Research